WHITE SUPREMACISTS DECEPTIVELY USING SCREENSHOTS AS EVIDENCE: A SOCIAL SEMIOTIC APPROACH TO ANALYSING CONSPIRATORIAL YOUTUBE VIDEOS - Inwood, Olivia (AoIR Selected Papers of Internet Research, 2021)
YouTube has become notoriously associated with extreme right-wing communities that spread discourses of white supremacy and conspiracy. This study applies a social semiotic approach to analysing conspiratorial YouTube videos created by white supremacists in response to the Notre Dame Fire of 2019. In particular, this study applies a combined legitimation (Van Leeuwen, 2007) and communing affiliation (Zappavigna and Martin, 2018) framework to the verbal and visual content of 15 videos. Communing affiliation refers to how values are positioned as bondable in situation where users don’t interact directly (Zappavigna and Martin, 2018). It is formed from couplings of ideational (what is being evaluated) and attitudinal (how it is evaluated) meaning (Martin and White, 2005), hence forming a value that is bondable. Legitimation (Van Leeuwen, 2007) refers to how discourses establish authority and can be realised textually or visually, with various linguistic strategies. This study will focus on the idea of ‘technological authority’ construed by positive evaluations in the transcripts of screenshots as evidence and the use of screenshots as visual evidence. Overall, this study will show how key values are working in tandem with (de)legitimation strategies, how (de)legitimation can further explain the significance of these values, and how YouTubers artificially create credibility in their videos through these legitimation and affiliation strategies. This raises further questions about the invoked meanings of screenshots as evidence and the ethical dilemmas that screenshots become entangled in, when considering the attention given to false and hateful content that is shared online.